Манюня, юбилей Ба и прочие треволнения - Абгарян Наринэ (Веселые истории, 2017)
Экземпляры: ф.18 (20190513) / Инвентарный номер: 3167 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 13 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44